Legal Responsibility for Medical Risks and Medical Negligence in The View of Health Law - Sidi, Redyanto (Berpusi Publishing, 2023)
This research examines legal aspects related to medical risk and negligence in the context of health law in Indonesia, especially after the ratification of Law Number 17 of 2023 concerning Health. Normative research methods are used, with a focus on examining legal principles, statutory regulations, relevant cases, and conceptual approaches in legal science related to medical negligence. The research results highlight that in criminal law, liability for medical acts deemed negligent depends on clear evidence of fault, in accordance with the principle